Reasons for the high rates of early retirement as received by retirement teachers in the region of Asir, Kingdom of Saudi Arabia - Al - Kiri, Yahya Ali Mansour (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the reasons for the high degree of availability of early retirement rates (the social dimension, and the psychological dimension, functional dimension, the physical dimension of health) by the teachers of Asir region, in addition, how the reasons for the high early retirement rates differences depending on personal information (educational stage where he worked, qualifications, the presence of additional income is teaching profession, and the health status. To achieve these goals, the researcher developed and applied a questionnaire on a convenience sample of teachers of Asir region (n= 588). Parametric statistical techniques were used to analyze study’s data such as mean, ANOVA, and T- test, the results were as follows: - All reasons for the high rates of early retirement (social dimension, the psychological dimension, functional dimension, the physical dimension of health and dimension) were moderately realized; the health dimension was the most , while the physical dimension was the least realized. - There are no statistically significant differences between the respondents’ responses to all the reasons for the high rates of early retirement due to the difference in phase of study, with the exception of the social, health dimensions and the dimension and the reasons for early retirement as a whole, in the favor of the middle school teachers. - There are no statistically significant differences between the respondents’ responses to all the reasons for the high rates of early retirement due to different qualification differences, with the exception of the psychological dimension in the favor of teachers with higher studies. - There are no statistically significant differences between the respondents’ responses on the reasons for the high rates of early retirement due to the difference in the additional income is teaching profession, except the physical dimension were in favor of whom with additional income is teaching profession - There are no statistically significant differences between the respondents’ responses on the reasons for the high rates of early retirement due to the difference in health status, except health dimension were differences for the benefit of those who have the disease. The researcher proposed some recommendations according to the study’s results as well as some suggested future studies.